Allocating Decision-Making Powers Among Creditor Classes: The Ups and Downs of Battling Claims Heterogeneity in Czech Corporate Insolvency Law. (14th January 2014) - Richter, Tomáš
Abstract The problem of claims heterogeneity makes allocating decision-making powers an arduous task for any insolvency law that aims to vest control over corporate insolvency proceedings in the creditors. The Czech Insolvency Act 182/2006 is a case in point. One of the Act's chief reform aims was to take control over the proceedings away from the hands of the judges and insolvency trustees and vest it in the creditors. Five years after the Act entered into force, it is time to look at how it succeeded in its ambition. This article reviews the rules allocating decision-making powers between secured and unsecured creditors in relation to several key 'turningpoints' in Czech insolvency proceedings, and also looks at how the initial rules were interpreted and applied by the insolvency courts. It also points to a set of amendments adopted by the Czech Parliament in the autumn of 2013 with a view to codifying those interpretive approaches that were found to work, as well as reversing those where the insolvency judiciary was thought to have drifted away from the original intentions of the Act. In particular, the article looks at creditors' decisions on (a) the type of proceedings, (b) the appointment, removal, powers and conflicts of the insolvency trustee, (c) the election and removal of the creditors' committee, and (d) the assumption of the creditors' committee's powers by the creditors' meeting. The article is limited to rules applicable to corporate debtors.